ANALISIS PENERAPAN DAN PERKEMBANGAN PRO-POOR BUDGETING DI PROVINSI SUMATERA SELATAN TAHUN 2009-2013 - Padriyansyah Padriyansyah (Universitas Indo Global Mandiri)
This study aimed to analyze the application and development of pro-poor budgeting in the province of South Sumatra, which is done by analyzing the consistency, relevance and effectiveness of pro-poor budgeting documents between government development planning and budgeting. The analysis technique used is descriptive analysis of qualitative and quantitative research to answer the problem. The results showed that the application of the assessment ratio of pro-poor budgeting calculations obtained 0.2 in 2009, 2010 and 2011 with a very pro category. Whereas, in the implementation of pro-poor budgeting in 2012 and in 2013 obtained the calculation of 0.18 with enough categories siding.